2008
DOI: 10.1073/pnas.0810657105
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for binding multiple ATPs to convert a GroEL ring to the folding-active state

Abstract: Production of the folding-active state of a GroEL ring involves initial cooperative binding of ATP, recruiting GroES, followed by large rigid body movements that are associated with ejection of bound substrate protein into the encapsulated hydrophilic chamber where folding commences. Here, we have addressed how many of the 7 subunits of a GroEL ring are required to bind ATP to drive these events, by using mixed rings with different numbers of wild-type and variant subunits, the latter bearing a substitution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…After protein binding, the subsequent binding of ATP [52,82] can further unfold the substrate protein [10,11,44,52,64]. ATP binding also provides enough energy (roughly 46 kcal/mol per ring [83,84]) to allosterically free GroES [85], and possibly the substrate protein (yellow) from the opposite ring, less than 1 s later [52]. The subsequent binding of GroES to the top ring eventually frees the protein from the opening of GroEL and into the newly formed ''cis'' chamber, where it can continue folding [10,11,21,40,52,[64][65][66][67][68]86].…”
Section: Substrate Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…After protein binding, the subsequent binding of ATP [52,82] can further unfold the substrate protein [10,11,44,52,64]. ATP binding also provides enough energy (roughly 46 kcal/mol per ring [83,84]) to allosterically free GroES [85], and possibly the substrate protein (yellow) from the opposite ring, less than 1 s later [52]. The subsequent binding of GroES to the top ring eventually frees the protein from the opening of GroEL and into the newly formed ''cis'' chamber, where it can continue folding [10,11,21,40,52,[64][65][66][67][68]86].…”
Section: Substrate Characterizationmentioning
confidence: 99%
“…2a and 4, sideways arrows). ATP binding and consumption provides the energy for GroEL to repeatedly bind to proteins, denature them, and (sometimes) release them [40,44,[82][83][84][85]. Stringent GroEL-dependent proteins typically endure many such ATPase cycles before folding [13] (see also [7,16,80,91,102]).…”
Section: The Anfinsen Cage Model (Passive Cage)mentioning
confidence: 99%
“…One strategy aims at targeting HSP60 cysteine residues either as oxidizable sites [128] or for covalent binding, presumably through interaction with an electrophilic compound [129][130][131]. The other approach targets ATP binding and hydrolysis sites-functions, thus affecting those ATP-dependent conformational changes of HSP60 which are crucial for the protein folding function [132][133][134].…”
Section: Hsp60 Inhibitors and Their Potential Applications In Alzheimmentioning
confidence: 99%
“…4.6, left) -can form a complex with HSP60 thus affecting its protein-folding activity [132,133]. A recent study further showed that mizoribine (6) slowed down the folding cycle by affecting ATP hydrolysis.…”
Section: Hsp60 Inhibitors and Their Potential Applications In Alzheimmentioning
confidence: 99%
See 1 more Smart Citation